Growth and production of cucumber (Cucumis sativus L.) that cultivaed using various types of mulch and different doses of goat manure - Khoirunnisa, Futichat A’mila; Fuskhah, Eny (Jurnal Online Pertanian Tropik, 2019)
Improvement of cultivation techniques and increasing soil fertility through the use of fertilizers need to be considered to produce maximum cucumber plant growth and production. The research was aimed to examine the response of the growth and production of cucumber plants that cultivated using various types of mulch and different doses of goat manure. The research was conducted on March - June 2019 at the Merbuh Village, Singorojo sub-district, Kendal district of Central Java Province. A block randomized design factorial pattern 3 x 4 with three replications was used throughout the experiment. The first factor consisted of treatment without mulch (M0), rice straw mulch (M1) and black silver plastic mulch (M2). The second factor consisted of 4 levels of Nitrogen doses including P0 = Nitrogen, phosphorus, and potassium (NPK) recommendation for cucumber plant 160 kg N/ha; P1 = 177 kg N/ha; P2 = 354 kg N/ha; P3 = 531 kg N/ha respectively equal to 0, 10, 20, and 30 tons of manure/ha. The data obtained were analyzed using analysis of variance (ANOVA), and a further test was carried out on the parameters that showed a significant difference in the mean values of the treatment using the Duncan test. The results showed that the treatment of silver black plastic mulch increased the growth and production of cucumber plants. The treatment of goat manure at a dose of 10 tons/ha had been able to increase all parameters and goat manure with a dose of 30 tons/ha gave high results on all parameters of cucumber plants compared to that of the control. The treatment of black silver plastic mulch with a goat manure dose of 30 tons/ha gave high results in the number of fruit parameters.